- PELAKSANAAN PENJAMINAN SISTEM RESI GUDANG PADA PERSEROAN TERBATAS JAMINAN KREDIT INDONESIA: - - Ersya Maulina; Listyowati Sumanto (Faculty of Law, Universitas Trisakti, 2023)
One of Indonesia's strengths lies in its abundant natural resources. In the agricultural sector, surplus stock arises from plentiful harvests exceeding market demand. Farmers are compelled to sell well below market prices, unwilling to risk marketing low-quality or unprofitable yields. Law Number 9 of 2011 on the Warehouse Receipt System provides a government solution. The research examines the implementation of PT Jamkrindo's warehouse receipt guarantee system concerning holders and collateral recipients when warehouse management fails. It explores challenges faced by PT Jamkrindo in protecting the rights of warehouse receipt holders and collateral recipients in the event of warehouse management bankruptcy. Employing a normative juridical research approach, descriptive and qualitative analyses using secondary data, the study concludes that in bankruptcy cases, legal protection is afforded to warehouse receipt holders and collateral recipients, enabling them to seek compensation through legal claims. Challenges for PT Jamkrindo include difficulty in finding an ideal warehouse manager, limited facilities and infrastructure, and the absence of a comprehensive guarantee mechanism covering overall losses, especially during warehouse manager bankruptcy.